The Effect of Executive Stock Option Plans on Stockholders and Bondholders - DeFUSCO, RICHARD A.; JOHNSON, ROBERT R.; ZORN, THOMAS S. (Journal of Finance, 1990)
ABSTRACT Executive stock option plans have asymmetric payoffs that could induce managers to take on more risk. Evidence from traded call options and stock return data supports this notion. Implicit share price variance, computed from the Black‐Scholes option pricing model, and stock return variance increase after the approval of an executive stock option plan. The event is accompanied by a significant positive stock and a negative bond market reaction. This evidence is consistent with the notion that executive stock options may induce a wealth transfer from bondholders to stockholders.